1990
DOI: 10.1007/bf00312611
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and expression of two ?-amylase genes from Aspergillus niger var. awamori

Abstract: Using synthetic oligonucleotide probes, we cloned genomic DNA sequences encoding an alpha-amylase gene from Aspergillus niger var. awamori (A. awamori) on a 5.8 kb EcoRI fragment. Hybridization experiments, using a portion of this cloned fragment to probe DNA from A. awamori, suggested the presence of two alpha-amylase gene copies which were subsequently cloned as 7 kb (designated as amyA) and 4 kb (amyB) HindIII fragments. DNA sequence analysis of the amyA and amyB genes revealed the following: (1) Both genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Overall, AsTaaG1 showed significant sequence identity to other Aspergilli α-amylases. AsTaaG1 showed 97.4% identity to Aspergillus awamori AmyA (Korman et al, 1990), 98.4% to A. flavus AFLA_026140A (Payne et al, 2006), 78.2% to Aspergillus fumigatus amylase (Nierman et al, 2005), 97.8% to Aspergillus kawachii AmyA (Nagamine et al, 2003), 69.5% to Aspergillus niger An04g06930 (Pel et al, 2007), 69.5% to A. nidulans AN2018.2 (Galagan et al, 2005), 98.2% to A. oryzae TaaG1 (Tsukagoshi et al, 1989), 97.8% to A. oryzae TaaG2 (Tsukagoshi et al, 1989), 97.6% to Aspergillus shirousami Amy (Shibuya. et al, 1992).…”
Section: Amplification Of the Astaag1 Gene And Its Cdna By Pcr And Rtmentioning
confidence: 99%
“…Overall, AsTaaG1 showed significant sequence identity to other Aspergilli α-amylases. AsTaaG1 showed 97.4% identity to Aspergillus awamori AmyA (Korman et al, 1990), 98.4% to A. flavus AFLA_026140A (Payne et al, 2006), 78.2% to Aspergillus fumigatus amylase (Nierman et al, 2005), 97.8% to Aspergillus kawachii AmyA (Nagamine et al, 2003), 69.5% to Aspergillus niger An04g06930 (Pel et al, 2007), 69.5% to A. nidulans AN2018.2 (Galagan et al, 2005), 98.2% to A. oryzae TaaG1 (Tsukagoshi et al, 1989), 97.8% to A. oryzae TaaG2 (Tsukagoshi et al, 1989), 97.6% to Aspergillus shirousami Amy (Shibuya. et al, 1992).…”
Section: Amplification Of the Astaag1 Gene And Its Cdna By Pcr And Rtmentioning
confidence: 99%
“…Since the N-terminal amino acid was not methionine but leucine, it turns out that N-terminal of Amyl III was processed. When the identified N-terminal amino acid sequence was compared to the existing sequences in the database, acid α-amylase of A. niger (Korman et al, 1990) showed 7 identical residues. Internal amino acid sequences of the fragments produced by peptidase digestion of Amyl III were TITYDWDADLV and SLSDALHRGMWL.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid sequence similarity The amino acid sequence of Amyl III has 93% homology with the acid α-amylase from A. niger (Korman et al, 1990). On the other hand, the homology with α-amylase from Aspergillus sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…niger var. awarnori [44] which show very high sequence identity in both exons and introns. The three highly similar Mucor racernosus EF-la genes share one intron that also shows a high sequence identity, whereas a second intron, that is present at identical positions but is not conserved in sequence, is found in only two of these genes [45].…”
Section: Discussionmentioning
confidence: 99%